HUBUNGAN AKTIVITAS FISIK DENGAN GANGGUAN MENSTRUASI WANITA PASANGAN USIA SUBUR DI DESA TEMANGGUNG KECAMATAN KALIANGKRIK KABUPATEN MAGELANG TAHUN 2015 - Anindita Mahitala (Jurnal Kesehatan Masyarakat (Undip), 2017)
Sustainable menstrual disorders caused disruption in reproductive system that lead to various diseases such as increased risk of cervical cancer, breast cancer, and infertility. Women in Temanggung village who do not have a child experienced menstrual disorders by 7 of 10 people, the most influential factor is physical activity .The purpose of this study was to analyze the relationship between physical activity and menstrual disorders to women in productive couples. The method used explanatory research with cross sectional study. The population were women in productive couples who do not have a child, in total of 71 people and those were selected by simple random sampling of 51 people. Data analysis includes univariate and bivariate (descriptive and analytic). The results of the univariate analysis showed the percentage of heavy physical activity at (64,7%) and the percentage of menstrual disorders women in productive couples is (60,8%). Bivariate descriptive analysis showed the greater percentage of menstrual disorders in heavy physical activity at (75,8%), and percentage of menstrual disorders happening was greater in mild and moderate activity is (66,7%). The results of the statistical test Chi square with continuity correction showed that relationship between physical activity and menstrual disorders to women in productive couples is (pvalue = 0.008).Advice given by health workers to women in productive couple in this case is counseling and physical activity measurements. Women in reproductive couple to reduce activity and maintain adequate rest patterns.